Relationship between delivery with anesthesia and postpartum depression: The Japan Environment and Children's Study (JECS) - Nobuhiro Suzumori; Takeshi Ebara; Hazuki Tamada; Taro Matsuki; Hirotaka Sato; Sayaka Kato; Shinji Saitoh; Michihiro Kamijima; Mayumi Sugiura-Ogasawara; the Japan Environment, Children's Study Group (BMC, 2021)
Abstract Background Postpartum depression is one of the most commonly experienced psychological disorders for women after childbirth, usually occurring within one year. This study aimed to clarify whether women with delivery with anesthesia, including epidural analgesia, spinal-epidural analgesia, and paracervical block, had a decreased risk of postpartum depression after giving birth in Japan. Methods The Japan Environment and Children's Study (JECS) was a prospective cohort study that enrolled registered fetal records (n = 104,065) in 15 regions nationwide in Japan. Binomial logistic regression analyses were performed to calculate the adjusted odd ratios (aORs) for the association between mode of delivery with or without anesthesia and postpartum depression at one-, six- and twelve-months after childbirth. Results At six months after childbirth, vaginal delivery with anesthesia was associated with a higher risk of postpartum depression (aOR: 1.233, 95% confidence interval: 1.079-1.409), compared with vaginal delivery without analgesia. Nevertheless, the risk dropped off one year after delivery. Among the pregnant women who requested delivery with anesthesia, 5.1% had a positive Kessler-6 scale (K6) score for depression before the first trimester (p < 0.001), which was significantly higher than the proportions in the vaginal delivery without analgesia (3.5%). Conclusions Our data suggested that the risk of postpartum depression at six months after childbirth tended to be increased after vaginal delivery with anesthesia, compared with vaginal delivery without analgesia. Requests for delivery with anesthesia continue to be relatively uncommon in Japan, and women who make such requests might be more likely to experience postpartum depressive symptoms because of underlying maternal environmental statuses.